First-Principles Elastic and Anisotropic Characteristics of Structure-H Gas Hydrate under Pressure - Shaden M. Daghash (Crystals, 2021)
Evaluating gas hydrates properties contributes valuably to their large-scale management and utilization in fundamental science and applications. Noteworthy, structure-H (sH) gas hydrate lacks a comprehensive characterization of its structural, mechanical, and anisotropic properties. Anisotropic and pressure dependent properties are crucial for gas hydrates’ detection and recovery studies. The objective of this work is the determination of pressure-dependent elastic constants and mechanical properties and the direction-dependent moduli of sH gas hydrates as a function of guest composition. First-principles DFT computations are used to evaluate the mechanical properties, anisotropy, and angular moduli of different sH gas hydrates under pressure. Some elastic constants and moduli increase more significantly with pressure than others. This introduces variations in sH gas hydrate’s incompressibility, elastic and shear resistance, and moduli anisotropy. Young’s modulus of sH gas hydrate is more anisotropic than its shear modulus. The anisotropy of sH gas hydrates is characterized using the unit cell elastic constants, anisotropy factors, and the angular dependent moduli. Structure-properties composition correlations are established as a function of pressure. It is found that compressing filled sH gas hydrates increases their moduli anisotropy. Differences in atomic bonding across a crystal’s planes can be expected in anisotropic structures. Taken together the DFT-based structure–properties–composition relations for sH gas hydrates provide novel and significant material physics results for technological applications.